2013
DOI: 10.1016/j.bpj.2013.10.026
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Semidisorder in Temperature Adaptation of Bacterial FlgM Proteins

Abstract: Probabilities of disorder for FlgM proteins of 39 species whose optimal growth temperature ranges from 273 K (0°C) to 368 K (95°C) were predicted by a newly developed method called Sequence-based Prediction with Integrated NEural networks for Disorder (SPINE-D). We showed that the temperature-dependent behavior of FlgM proteins could be separated into two subgroups according to their sequence lengths. Only shorter sequences evolved to adapt to high temperatures (>318 K or 45°C). Their ability to adapt to high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…However, contradicting their predictions, they observed that thermophiles often are depleted in IDRs, which may compensate for the disorder induced by temperature. Similar observations were made in both another proteome-level analysis [15] and an analysis of FlgM proteins from bacteria adapted to different temperatures [14]. In agreement with Burra et al’s prediction, we observed that Arabidopsis heat-induced proteins are enriched in IDRs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, contradicting their predictions, they observed that thermophiles often are depleted in IDRs, which may compensate for the disorder induced by temperature. Similar observations were made in both another proteome-level analysis [15] and an analysis of FlgM proteins from bacteria adapted to different temperatures [14]. In agreement with Burra et al’s prediction, we observed that Arabidopsis heat-induced proteins are enriched in IDRs.…”
Section: Discussionsupporting
confidence: 92%
“…A few studies in prokaryotes have also shown that thermophile proteins are depleted in intrinsically disordered regions (IDRs), i.e., regions that lack a defined three-dimensional structure [ 13 , 14 , 15 ]. This observation is consistent with the fact that high temperatures induce disorder, but in contrast with the fact that IDRs confer thermoresistance [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%